Developing a Wave Energy Converter in Offshore Environments with Sea Ice: Techno-Economic Assessment of a Point Absorber in Sea Ice - Kolset, Alexander (author) (2024)
In recent years, there has been growing interest in exploring the deployment of wave energy converters (WECs) in remote and harsh environments. However, research in this area remains limited, particularly concerning offshore environments with sea ice. This study focuses on investigating the energy production and economic feasibility of a point absorber in the Baltic Sea, specifically off the coast of Åland, which experiences seasonal ice cover. Four winter seasons with varying ice conditions are examined, ranging from ice-free to severe ice conditions. Additionally, the study aims to assess the survivability of the WEC under extreme level ice action and extreme wave conditions. Based on literature review, a hexagonal slope-shaped buoy has shown promise in withstanding ice conditions up to 15 cm thickness in the Baltic Sea and is selected as the WEC design in this study. Metocean and sea ice data spanning from 2006 to 2021 are analysed from the NORA3 database. Through extreme value analysis, key parameters such as wave height, period, and ice thickness are determined. Survivability analysis is conducted to understand the forces exerted on the WEC during extreme ice load cases and extreme sea states. To evaluate energy production, hydrodynamic coefficients are computed using the Boundary Element Method solver Capytaine in the frequency domain. Subsequently, simulations are conducted using WEC-Sim to derive the power output of the WEC under varying sea states. Optimisation of the Power Take-Off (PTO) damping is performed to enhance performance for the specific site conditions. A comparison of power output is made among different WEC configurations with varying translator sizes. The survivability analysis reveals important design considerations, especially regarding extreme ice conditions. When subjected to an extreme level ice thickness of 60 cm this results in calculated horizontal and vertical forces of 615 kN and 315 kN, respectively. In extreme sea states, simulations in WEC-Sim shows a maximum heave response ...